PENGARUH SELF CONFIDENCE TERHADAP ENTREPRENEURSHIP PADA GENERASI MILENIAL DI KOTA DEPOK - Zinedine Zidane Fawwaz; Siti Mahmudah; Hawabi Iqbal Agus (Jurnal Psikologi, 2024)
The Indonesian government is currently encouraging the development of entrepreneurship among the millennial generation. The country is experiencing a demographic bonus with 60% of the population in the age range of 15-64 years. Self-confidence is identified as a factor that influences entrepreneurship. the total population that is the focus of the study is 14,136 millennial entrepreneurship in Depok City. Sampling was conducted randomly using the random sampling method using the Slovin calculation, and a tolerable error rate of 5%. As a result, the number of respondents involved in this study was 390 entrepreneurs from the millennial generation. In the data analysis test stage, a description test, assumption test, and hypothesis testing were carried out. The normality test results show that the data distribution is normal, and the linearity test confirms that the data is linear. The t-test shows that partially, self confidence has a significant positive effect on entrepreneurship. The f test, which is conducted simultaneously, shows that the self confidence variable significantly affects the entrepreneurship variable. In the simple linear regression analysis, it was found that the significance value of the coefficient is 0.05%, which means that self confidence has a positive and significant influence on entrepreneurship. The coefficient of determination of 34% indicates that self confidence contributes 34% to entrepreneurship. Thus, based on the results of data analysis and data processing, it can be concluded that the hypothesis in this study is accepted.